Semantic web technologies : research and applications - Patel, Archana (Lecturer in software engineering); Debnath, N. C. (Narayan C.); Bhushan, Bharat, 1989- (Boca Raton : CRC Press, 2023)
"Semantic web technologies (SWTs) offer the richest machine-interpretable (rather than just machine-processable) and explicit semantics that are being extensively used in various domains and industries. This book provides a roadmap for Semantic Web Technologies (SWTs) and highlights their role in wide range of domains including Cloud Computing, Internet of Things, Big data, Sensor Network, and so forth. It also explores the prospects of these technologies including different data interchange formats, query languages, ontologies, Linked Data, and notations. The role of SWTs in 'Epidemic Covid-19', 'E-Learning platforms and systems', 'Block chain', 'Open online courses', and 'Visual analytics in Healthcare' is described as well. Explores all the critical aspects of semantic web technologies (SWT) Discusses impact of SWTs on cloud computing, Internet of things, big data, and sensor network Offers a comprehensive examination of the emerging research in the areas of SWTs and their related domains Provides a template to develop a wide range of smart and intelligent applications Includes latest applications and examples with real data This book is aimed at Researchers and graduate students in Computer Science, Informatics, Web Technology, Cloud Computing, and Internet of Things"--
Semantic web technologies / Esingbemi P. Ebietomere & Godspower O. Ekuobase -- Leveraging semantic web technologies for veracity assessment of big biodiversity data / Zaenal Akbar, Yulia A. Kartika, Dadan R. Saleh, Hani F. Mustika, Lindung P. Manik, Foni A. Setiawan & Ika A. Satya -- Semantic web technologies : latest industrial applications / Michael DeBellis -- Latest applications of semantic web technologies for service industry / Godspower Osaretin Ekuobase & Esingbemi Princewill Ebietomere -- Semantic web ontology centred university course recommendation scheme / Gina George & Anisha M. Lal -- Exploring reasoning for utilizing the full potential of semantic web / Ayesha Ameen, Khaleel Ur Rahman Khan & B.Padmaja Rani -- Ontology modeling : an overview of semantic web ontology formalisms and engineering approaches with editorial tools / Olaide N. Oyelade -- Semantic annotation of objects of interest in digitized herbarium specimens for fine-grained object classification / Zaenal Akbar, Wita Wardani, Taufik Mahendra, Yulia A. Kartika, Ariani Indrawati, Tutie Djarwaningsih, Lindung P. Manik & Aris Yaman -- UpONto : strategic conceptual ontology modelling for unit operations in chemical industries and their retrieval using firefly algorithm / Ayush Kumar A & Gerard Deepak -- Ontologies for knowledge representation : tools and techniques for building ontologies / Ayesha Banu -- Data science and ontologies : an exploratory study / Prashant Kumar Sinha & Shiva Shankar Mahato -- Ontology application to constructing the GMDH-based inductive modeling tools / Halyna Pidnebesna & Volodymyr Stepashko -- Exploring the contemporary area of ontology research : FAIR ontology / Prashant Kumar Sinha -- Analysis of ontology based semantic association rule mining / G.Jeyakodi & P.Shanthi Bala -- Visualizing chat-bot knowledge graph using RDF / Noman Islam, Darakhshan Syed, Mariz Zafar & Asif Raza -- Towards data integration in the era of big data : role of ontologies / Houda El Bouhissi, Archana Patel & Narayan C. Debnath.
OCLC-licensed vendor bibliographic record.
Keywords: Semantic Web; COMPUTERS / Database Management / Data Mining; COMPUTERS / Programming / Systems Analysis & Design; COMPUTERS / Internet / General